SEGUIMIENTO DE UNA INNOVACIÓN CURRICULAR: UNA ASIGNATURA DE MATEMÁTICAS - Rondero-Guerrero, Carlos; Reyes-Rodríguez, Aarón; Acosta-Hernández, Juan Alberto (European Scientific Journal, ESJ, 2015)
In this paper we propose an emerging framework that can be useful for monitoring a curricular innovation, considering as an element of analysis the fulfillment of the innovation’s objectives and its coherence with the proposed educative paradigm, into a setting of a mathematics course, which was designed to solve a problem of high failure rates in college calculus courses. It is emphasized the influence of variables that impact on the students’ construction of mathematical knowledge and the shift of paradigm.